Pengaruh Kemampuan Akademik dan Beban Kerja Terhadap Disiplin Kerja Guru di SMK Negeri 1 Percut Sei Tuan Kabupaten Deli Serdang - Netti Erni; Ernita Sibuea; Dedi Ahmad Yani; Zilfaizah Nasution; Elfrianto Elfrianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of academic ability and workload on the work discipline of teachers. This research is quantitative with a survey method and has a sample of 54 respondents. Determination of the sample using probability sampling technique with simple random sampling method. Data collection techniques were carried out using interview techniques, documentation, and the distribution of questionnaires to respondents. Testing validity, reliability, and classical assumption tests are carried out in data processing techniques. Data analysis techniques were carried out by multiple linear regression and correlation coefficient analyses. Hypothesis testing is done by t-test (partial), f-test (simultaneous), and test the coefficient of determination. The results showed that: the results of the t-test (partial) for the academic ability variable obtained t-count (4.031) > t-table (1.675) and Sig 0.000 <0.05. This shows that academic ability has a positive and significant effect on the work discipline of teachers; the results of the t (partial) workload variable test obtained t-count (4.225) > t-table (1.675) and Sig 0.000 <0.05. This shows that workload has a positive and significant effect on teacher work discipline; f test results (simultaneous) obtained f - count (317.740) > f - table (3.18) and sig 0.000 <0.05. This shows that academic ability and workload positively and significantly affect teacher work discipline. In conclusion, there is an influence of academic ability and workload on teacher work discipline. Keywords: Academic Ability, Teacher Work Discipline, Workload